Expert Opinion on the Role of Sacubitril/Valsartan in the Management of Hypertension in India - Uday M. Jadhav; Saumitra Ray; T. Govindan Unni; J. P. S. Sawhney; Ashwani Mehta; Shantanu Guha; Rajiv D. Karnik; Bhupen N. Desai; Aziz Khan; Keyur Patel; Jayesh S. Prajapati; Hitesh J. Shah; et al. (Cardiology and Therapy)
Abstract Hypertension, a key modifiable risk factor for cardiovascular diseases (CVD), significantly contributes to premature death and morbidity worldwide. Despite stabilization in age-adjusted global prevalence, the absolute number of hypertensive individuals doubled from 2000 to 2010, largely due to increases in low- and middle-income countries. In 2021, only 21% of hypertensive individuals globally had effective blood pressure (BP) control. In India, hypertension is the leading risk factor for death and disability, with prevalence rates of 24% in men and 21% in women, as reported by the 2019–2020 National Family Health Survey (NFHS-5). Alarmingly, just 25% of rural and 38% of urban hypertensive Indians are undergoing treatment, with only 10% and 20% achieving BP control, respectively. This highlights the hypertension paradox, where clinical inertia and hesitancy in intensifying BP-lowering therapy persist despite the availability of antihypertensive drugs. This expert opinion paper aims to provide a comprehensive evaluation of sacubitril/valsartan in hypertension management, leveraging insights from its approved use in heart failure and examining its benefits and challenges across diverse hypertensive populations. The formulation of this expert opinion involved employing evidence-based methodologies and utilizing all available data. The document underwent scrutiny by expert cardiologists, whose clinical experiences and examination of the evidence and guidelines informed the formation of the expert opinion. This expert opinion paper provides a thorough and informed evaluation of sacubitril/valsartan, highlighting its potential to address unmet needs in BP control, particularly in challenging cases such as resistant hypertension and chronic kidney disease.